2016
DOI: 10.3389/fendo.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic Steroids as Modulators of Neuroinflammation

Abstract: Cardiotonic steroids (CTS) are a class of specific ligands of the Na+, K+- ATPase (NKA). NKA is a P-type ATPase that is ubiquitously expressed and although well known to be responsible for the maintenance of the cell electrochemical gradient through active transport, NKA can also act as a signal transducer in the presence of CTS. Inflammation, in addition to importantly driving organism defense and survival mechanisms, can also modulate NKA activity and memory formation, as well as being relevant to many chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 121 publications
(164 reference statements)
2
32
0
7
Order By: Relevance
“…Besides that, ouabain effects on CNS could be associated with its role in bipolar and depressive disorders (Goldstein et al, 2006 ; Tonin et al, 2014 ). The interaction between neuroinflammation and cardiac steroids is more substantially detailed by Orellana et al ( 2016 ).…”
Section: Ouabain As a Modulator Of Inflammationmentioning
confidence: 99%
“…Besides that, ouabain effects on CNS could be associated with its role in bipolar and depressive disorders (Goldstein et al, 2006 ; Tonin et al, 2014 ). The interaction between neuroinflammation and cardiac steroids is more substantially detailed by Orellana et al ( 2016 ).…”
Section: Ouabain As a Modulator Of Inflammationmentioning
confidence: 99%
“…These signals result in the activation of the inflammatory-associated transcription factor NF-κB and the subsequent production of inflammatory cytokines. In contrast, however, several reports showed that ouabain has the ability to suppress the production of inflammatory cytokines, suggesting an anti-inflammatory effect of cardiac glycosides [7]. Thus, the precise role of the Na + /K + -ATPase in inflammation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ouabain exhibited therapeutic effects on JEV infection in an adult mouse model by decreasing viral loads and alleviating pathological injuries in the brain, which significantly improved the survival rate of JEV-infected mice. Some evidence suggested that cardiac glycosides mediate inflammatory processes via the activation of the phosphoinositide 3-kinase/Akt pathway and the Src/mitogen-activated protein kinase pathway (28,29). First, ouabain may block JEV infection by inducing the cellular stress response.…”
Section: Ouabain Blocks Jev Infectionmentioning
confidence: 99%